Mitigation of WIP-related problems at an IC production line through a suitable inspection sampling plan - Karim, A.N. Mustafizul; Abd. Rahman, Mohamed; Hj. Yusop, Nornilawati (2014)
Unpredictable work-in-process (WIP) inventory developed in the inspection area of an integrated circuit (IC) assembly line due to the acceptance criteria dictated by a single sampling plan often requires additional human resources and results in longer production lead time. Sudden need of additional operators to carry out 100% inspection of the rejected lot creates an uneasy and difficult situation for the concerned manager. Securing outgoing quality of the ICs without increasing the production lead time and allocation of additional human resources appears to be a major challenge. Upon a critical study of a real-life assembly line, several sampling plans (double and multiple) which could adequately meet the current average outgoing quality limit (AOQL), a parameter indicating the level of outgoing lot quality, were applied. A multiple sampling plan was suggested to minimize the WIP level with a reduction in consequential effect on the line of operation. The proposed multiple sampling plan is expected to increase the average total inspection (ATI) but the benefits to be accrued through minimization of WIP level and the minimized resources in tackling the situation should outweigh the efforts for additional inspection involving only visual observation without carrying out any expensive destructive tests.